Alterations of theta power and synchrony during encoding in young adult binge drinkers: Subsequent memory effects associated with retrieval after 48 h and 6 months - Huang, Siyuan; White, David R.; Marinkovic, Ksenija (Frontiers in Psychology, 2022)
Young emerging adults commonly engage in binge drinking which is associated with a range of neurocognitive deficits, including memory impairments. However, evidence on neural oscillations mediating episodic memory in this population is lacking. To address this gap, we recorded theta oscillatory activity in young binge (BDs) and light drinkers (LDs) during memory encoding and analyzed it prospectively as a function of subsequent retrieval. Theta underlies successful encoding of novel items in memory through corticolimbic integration. Subsequent memory effects (SMEs) are reflected in stronger theta activity during encoding of the items that are later remembered compared to those that are later forgotten. In the present study, thirty-four BDs (age: 23.3 ± 3.3) and thirty-four LDs (age: 23.4 ± 3.3) rated emotionally evocative images with negative, positive, and neutral themes during implicit encoding. They performed a recognition memory task on two follow-up occasions after a short (48 hours), and long retention delay (6 months). Electroencephalography (EEG) signal was recorded during the encoding session and analyzed in time-frequency domain with Morlet wavelets in theta band (4-7 Hz). To evaluate SMEs, the event-related theta oscillations acquired during encoding were analyzed based on recognition outcomes after the two retention intervals. The BD and LD groups did not differ on recognition memory. However, BDs showed attenuated event-related theta power during encoding of images that were successfully retained after 6 months compared to LDs. In addition, theta synchronous activity between frontal and left posterior regions during encoding successfully predicted recognition of the images after both retention delays in LDs but not in BDs. These SMEs on theta power and synchrony correlated negatively with high-intensity drinking in the previous six months. It has been well established that long-range neural synchrony between cortical and limbic nodes underlies successful memory encoding and retention which, in turn, depends on neural excitation/inhibition (E/I) balance. Given that binge drinking is associated with E/I dysregulation, the observed SME deficiencies are consistent with other evidence of neural hyperexcitability in BDs, and may be indicative of increased risk of developing alcohol use disorders.